On experimental results and explicit exact solutions for the generalized Boussinesq type equation - Kaya, D (Elsevier Science Inc, 2005)
We implemented a decomposition method for approximating the solution of the generalized Boussinesq type equation. By using this scheme, the explicit exact solution is calculated in the form of a convergent power series with easily computable components. To illustrate the application of this method, numerical results are derived by using the calculated components of the decomposition series. The obtained results are found to be in good agreement with the exact solution. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: the decomposition method; the generalized Boussinesq type equations; traveling wave solution; solitary wave solution